Identification of Biomarkers Related to Prognosis of Bladder Transitional Cell Carcinoma - Liu, Zhihua; Xu, Lina; Lin, Youcheng; Hong, Huaishan; Wei, Yongbao; Ye, Liefu; Wu, Xiang (Frontiers in Genetics, 2021)
Bladder transitional cell carcinoma (BTCC) is highly fatal and generally has a poor prognosis. To improve the prognosis of patients with BTCC, it is particularly important to identify biomarkers related to the prognosis. In this study, differentially expressed messenger RNAs were obtained by analyzing relevant data of BTCC from The Cancer Genome Atlas (TCGA) and Gene Expression Omnibus (GEO) databases. Next, hub genes that were suitable for correlation analysis with prognosis were determined through constructing a protein-protein interaction (PPI) network of differentially expressed genes and screening of major modules in the network. Finally, survival analysis of these hub genes found that three of them (CCNB1, ASPM, ACTC1) were conspicuously related to the prognosis of patients with BTCC (p <0.05). By combining the clinical features of BTCC and the expression levels of the three genes, univariate Cox and multivariate Cox regression analyses were performed and denoted that CCNB1 could be used as an independent prognostic factor for BTCC. This study provided accurate and effective biomarkers for the prognosis of BTCC as well as a theoretical basis for subsequent prognosis-related research.